Issues on comprehensive land use plan (CLUP) implementation the case of Quezon city - Leger, Silia (School of Urban and Regional Planning, University of the Philippines Diliman, 2017)
The Philippines is currently 12th in the world and 7th in Asia of countries with the most rapidly increasing population. Simultaneously with its rapid urbanization, urban centers and rural areas in the Philippines are increasingly becoming vulnerable to natural disasters such as cyclones, floods, earthquakes, etc. which pose a serious concern for the nation. This rapid urbanization also creates a national level concern about the sustainable use of its land and water resources because the benefits from land and water utilization should accrue not only to the generation of today, but also to the generation of tomorrow. Fortunately, in the Philippines, the Local Government Code of 1991 and Executive Order No.72 of President Fidel V. Ramos mandated all the Local Government Units (LGUs) in the country to prepare and implement a Comprehensive Land Use Plan (CLUP); and to enact the appropriate Zoning Ordinance (ZO) that would serve as an implementing tool of the CLUP. However, often the actual land use seems to deviate from the approved uses of the formulated CLUP and ZO. While there are numerous studies on Land Use and Land Use Dynamics in the Philippines at various levels in the country, what are lacking are assessment studies on the actual Implementation phase of the approved CLUP and ZO in local government units. It is response to this need that this research was undertaken. A case study approach with quantitative methods was adopted to assess the status of the original Quezon City CLUP and he ZO which has been in existence since 2000 and was last amended in 2004. The main objective of this study is to examine how land use planning in the Philippines address conflicts and issues that evolve from the implementation of the CLUP. This study focuses on one aspect of implementation, which is the occurrence of deviations from the said plan. This was done by reviewing QC's resolutions embodying actions on applications for deviation for the fifteen (15) year period from 2000 up to 2015. This research covers the assessment of the implication system which includes the legislative structure and the institutional capacity of the QC LGU; the implications of these deviations on housing in QC, specifically in the resettlement areas; and lastly, the proposed measures that QC LGU could adopt for the more rational implementation of the its CLUP and ZO. This Case Study concludes that the QC CLUP and the ZO remain vital tools for the orderly and optimal utilization of its land resources that could positively promote the general welfare and enhance the city's socio-economic conditions. To achieve this, however, there are factors in the current implementing system critical to effective plan implementation that need to be reviewed and analysed. These factors include the following: first, the framework and guidelines prescribed by the HLURB for the plan formulation and implementation process; second, the differences in knowledge, interests and agenda among the stakeholders such as the politicians, the local Councils, planners, LGU staff, developers, and residents; and most importantly the need for more rational decision making on the proposed changes in land uses, more particularly, through deviations in the CLUP. A further finding of this study is that deviations which happen during the implementation process of the CLUP and ZO, sometimes occur because they are permitted under the current implementing system for reasons that, initially are expected to bring about positive effects. However, over time, it turns out that hey negatively affect the availability and affordability of land for other needed and urgent uses such as housing at various levels. In the light of the above factors of the current implementing system of the QC CLUP and ZO, this study further concludes that the initial purpose of this Land management tool, which is to bring about the best and orderly utilization of land does not always achieve this or does not accomplish it as originally envisioned. Instead, the implementation of QC's CLUP and ZO seems to be veering towards Fiscal Zoning whereby the ZO is being utilized to accommodate new market forces and attract businesses that will bring about a healthier fiscal condition in the LGU. Furthermore, the grant of a number of deviations to, among others, achieve this type of zoning has affected the integrity of the plan.This research is significant because it gives new insights and perspectives on the implications of the process of implementing a land use plan, particularly the CLUP and ZO, by identifying critical factors in some of the implementation stages. Specially, it provides an opportunity for QC LGU to identify and analyse housing issues that arise from the issuance of deviation permits, and in response to them, develop new approaches toward a more effective implementation of the CLUP and its tools for carrying out the Plan.